Research of the operation of a group of asynchronous motors at short-term voltage slopes for the conditions of the oil industry - R. R. Sattarov; R. R. Garafutdinov (Известия высших учебных заведений: Проблемы энергетики)
Voltage dips are quite frequent and dangerous phenomenon, which can lead to disruption of the production process. Ensuring the stability of induction motors during voltage dips is an important task to ensure the continuity of the technological process, as well as to reduce material losses. THE PURPOSE. List the main causes of voltage dips. Develop a simulation model corresponding to a typical power supply scheme for an oil pumping station with a group of asynchronous motors as a load. Perform two series of calculations to determine the parameters of the electrical mode in case of voltage dips and the subsequent restoration of the voltage on the buses of the supply substation. METHODS. When solving the problem, the PSCAD software package was used. RESULTS. The article describes the relevance of the topic, the main causes of voltage dips are given. The simulation of voltage dips resulting from a short circuit on the substation equipment has been performed. A series of calculations were performed, differing from each other in the changed initial data: the place of occurrence of a short circuit, the time delay of automatic transfer of the reserve. The analysis of the obtained results is carried out. CONCLUSION. According to the test results, it can be seen that the decrease in voltage on the low voltage buses of substations after the operation of automatic transfer switch is the lower, the longer the time delay of automatic transfer switch. In this work, the maximum time delay was 7 seconds, while there was no violation of the stability of the induction motors. The need to study the operation of a group of asynchronous motors in case of accidents in an external electrical network is also determined.